Consumer myopia in vehicle purchases: Evidence from a natural experiment - Kenneth Gillingham; Sébastien Houde (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
A central question in the analysis of fuel-economy policy is whether consumers are myopic with regards to future fuel costs. We provide the first evidence on consumer valuation of fuel economy from a natural experiment. We examine the short-run equilibrium effects of an exogenous restatement of fuel-economy ratings that affected 1.6 million vehicles. Using the implied changes in willingness-to-pay, we find that consumers act myopically: consumers are indifferent between 1 in discounted fuel costs and 15-38 cents in the vehicle purchase price when discounting at 4%. This myopia persists under a wide range of assumptions.
Keywords: D12; H25; L11; L62; L71; Q4; 330; fuel economy; vehicles; myopia; undervaluation; regulation